2017
DOI: 10.1108/jbim-09-2015-0175
|View full text |Cite
|
Sign up to set email alerts
|

Renegotiations – empirical analysis of impacts on business relationships

Abstract: Purpose Renegotiations not only promise an economically relevant improvement of the original negotiation outcome for the communicator of the demand but also imply a potential threat to the business relationship. The purpose of this paper is to examine the impact of renegotiations in detail and to provide practical implications for the optimal usage of renegotiations by analyzing potential renegotiation strategies. Design/methodology/approach Structural equation modelling was used to analyze the data of 255 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Previous research has shown that both the conclusion (Halinen and Tähtinen, 2002) and the reactivation (Poblete, 2017) of business relationships are processes that take time and require effort. When doing business again with a former business partner, aspects such as price, product features, order quantities, quality levels, delivery scheduling, transportation arrangements and terms of payment might need to be negotiated (Liu et al, 2015;Voeth and Lenzing, 2017). Both parties may need to air experiences and knowledge about each other and discuss expectations regarding future business exchanges (Voeth and Lenzing, 2017;Rao and Perry, 2002).…”
Section: Relationship (Re-)building Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has shown that both the conclusion (Halinen and Tähtinen, 2002) and the reactivation (Poblete, 2017) of business relationships are processes that take time and require effort. When doing business again with a former business partner, aspects such as price, product features, order quantities, quality levels, delivery scheduling, transportation arrangements and terms of payment might need to be negotiated (Liu et al, 2015;Voeth and Lenzing, 2017). Both parties may need to air experiences and knowledge about each other and discuss expectations regarding future business exchanges (Voeth and Lenzing, 2017;Rao and Perry, 2002).…”
Section: Relationship (Re-)building Activitiesmentioning
confidence: 99%
“…When doing business again with a former business partner, aspects such as price, product features, order quantities, quality levels, delivery scheduling, transportation arrangements and terms of payment might need to be negotiated (Liu et al, 2015;Voeth and Lenzing, 2017). Both parties may need to air experiences and knowledge about each other and discuss expectations regarding future business exchanges (Voeth and Lenzing, 2017;Rao and Perry, 2002). This can be seen as a dialogue between representatives of the firms aimed at agreeing on different needs and goals for the future in the business relationship (Ariño and Reuer, 2004;Voeth and Lenzing, 2017).…”
Section: Relationship (Re-)building Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Teams also renegotiate. Voeth and Lenzing (2017) investigated the impact of teams' renegotiation on relationship continuity. The first step of the analysis pursued a better understanding of renegotiation outcomes and their impact on relationship continuity, and the second step analyzed the conceptualization and detailed negotiation strategies and their impacts on renegotiation results.…”
Section: Introductionmentioning
confidence: 99%